Perancangan Sistem Informasi Pengelolaan Bantuan Sosial Berbasis Web Pada Dinas Sosial Provinsi Sumatera Utara - Nabila, Siti Fadiyah; Tambak, Tiara Ayu Tiarta; Siahaan, Ahmad Taufik Al Afkari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The Social Service Office of North Sumatra Province is the agency responsible for managing social assistance in the region. In its implementation, the Social Service often faces various challenges, such as inaccuracies in data for assistance recipients, delays in the distribution of assistance, and a lack of transparency in the assistance distribution process. This research uses a systems design approach with qualitative and descriptive research methods. The systems design approach is chosen because this study aims to design a web-based social assistance management information system that can be used by the Social Service Office of North Sumatra Province. The results of the design of the web-based social assistance processing information system for People with Social Welfare Problems (PMKS) at the Office of People's Welfare SETDAPROVSU provide significant benefits, such as increased efficiency in online data processing, improved accessibility, and higher transparency.